Article Sistem Informasi Pengelolaan Masjid Darussalam GKB2 berbasis Web - Sigit Purnomo; Frandika Septa (Jurnal CoSciTech (Computer Science and Information Technology), 2021)
One computer-based information system is the website, usually in its online form. The amount of activity, financial management and data processing still conducted in manual bogies of difficulty. To address that problem requires easily accessible system of management, at any time, anywhere, precisely, fast and accurate by the mosque and community. On that basis it developed a web based mosque management information systems that are made with a PHP programming language, javascript and mysql database. The goal of the system is to make it easier for the mosque to manage the financial data, to manage activities of the mosque and to make it easier for the public to search for information on the existing website system. The sequence of these studies includes critical analysis, system desaign, implementation, testing and maintenance. The Darussalam mosque management system was tested by the black box method and focused on functional requirements using alpha testing. This research examination is still ina purely functionality testing phase incolving unintended objects can occur without specific testing especially on the interface part where ddynamic programming of the interface elements blending in using HTML and CSS presentation of documents. So in running the system as a web-based application, it should affect the web browser in running the system.